A conjunction of interests : business, politics, and tariffs, 1825-1879 - Forster, Jakob Johann Benjamin, 1949- (State and economic life, 1986)
The advent of the National Policy in 1879 brought dramatic changes in the structure, magnitude, and objectives of Canada's tariff policy. No longer used primarily as a source of revenue for the government, tariffs on imported goods assumed a role as protector of Canadian industry against the encroachment of foreign imports on the Canadian market.In this detailed account of events leading up to the adoption of the National Policy, Ben Forster explores a wide range of political and economic forces and races their influence on successive Liberal and Conservative governments. He examines the pamphlet literature of the protectionists, the private corespondence of political leaders and protectionists, the public press of the day, and legislative journals and other public documents. He weaves the threads of various interests - business, industry, agriculture, and government - into a comprehensive account of the growth of protectionist feeling in Canada.Forster's analysis illuminates a critical chapter in Canadian political history, one with implications for current discussions on import "as, industrial policy, and free trade.